2020
DOI: 10.1007/s11418-020-01431-8
|View full text |Cite|
|
Sign up to set email alerts
|

The search for, and chemistry and mechanism of, neurotrophic natural products

Abstract: Neurotrophic factors, now termed neurotrophins, which belong to a class of polypeptidyl agents, have been shown to potentially be beneficial for the treatment of neurodegenerative diseases such as Alzheimer's disease, because endogenous neurotrophic factors (NGF, BDNF, NT3, NT4) have been recognized to play critical roles in the promotion of neurogenesis, differentiation, and neuroprotection throughout the development of the central nervous system. However, high-molecular weight proteins are unable to cross th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 146 publications
(223 reference statements)
0
11
0
Order By: Relevance
“…Isorhamnetin-3-Oglucoside (1) and astragalin (2), which promote neurite outgrowth, also increased the neurofilament expression. The compounds promoting neurite outgrowth are thought to be effective for treating cognitive dysfunctions, such as Alzheimer's disease, by helping the differentiation of neurons associated with memory and learning in the brain [30]. Isorhamnetin-3-O-glucoside (1) and astragalin (2) have strong neurite outgrowth-promoting activities; however, they are metabolized by human intestinal flora to create aglycons [31].…”
Section: Promoting the Activity Of Isorhamnetin-3-o-glucosides (1) An...mentioning
confidence: 99%
“…Isorhamnetin-3-Oglucoside (1) and astragalin (2), which promote neurite outgrowth, also increased the neurofilament expression. The compounds promoting neurite outgrowth are thought to be effective for treating cognitive dysfunctions, such as Alzheimer's disease, by helping the differentiation of neurons associated with memory and learning in the brain [30]. Isorhamnetin-3-O-glucoside (1) and astragalin (2) have strong neurite outgrowth-promoting activities; however, they are metabolized by human intestinal flora to create aglycons [31].…”
Section: Promoting the Activity Of Isorhamnetin-3-o-glucosides (1) An...mentioning
confidence: 99%
“…Moreover, MN (1) and HK (2) are isomers, whose only difference is the relative position of one hydroxyl group and allyl group. The 4′-hydroxy group and the 5-allyl group are the key to higher neurotrophic activity of HK (2) than that of MN (1) ( Fukuyama et al, 2020 ). Furthermore, both HK (2) and MN (1) exerted neuroprotective effects, which might be related to penetrate the blood-brain barrier (BBB) ( Kantham et al, 2017 ).…”
Section: Chemistry Of Principal Bioactive Ingredients In Neolignansmentioning
confidence: 99%
“…[1,2] As such they have been touted as possible leads for the development of drugs to treat neurodegenerative diseases. [3] These features have prompted studies on their synthesis [4][5][6] and our efforts [4] in this regard led to the preparation of congeners 1-4 and so resulting in the confirmation of the structures assigned to ribisins A and D and corrections to those originally assigned to congeners B and C. Furthermore, prior to the report of the isolation of ribisin G by Dong et al [2] we had prepared this compound [4b] and have recently shown [7] that there is good agreement between the spectral data sets recorded on the naturally-and synthetically-derived materials. Since our synthetic studies on the ribisins had resulted in the generation of a suite of analogues [4] we evaluated these, as well as natural products 1-4 and 7, for their neuroprotective properties and thereby established [7] that certain analogues and derivatives of the ribisins are quite active in this regard and most likely exert their beneficial effects by activation of the Keap1-Nrf2-ARE pathway.…”
Section: Introductionmentioning
confidence: 99%
“…The structurally distinct benzofuran‐containing natural products 1 – 7 (Figure 1), named ribisins A–G respectively, have been isolated from the medicinal fungus Phellinus ribis and reported to exert nerve growth factor (NGF)‐potentiating activities [1,2] . As such they have been touted as possible leads for the development of drugs to treat neurodegenerative diseases [3] . These features have prompted studies on their synthesis [4–6] and our efforts [4] in this regard led to the preparation of congeners 1 – 4 and so resulting in the confirmation of the structures assigned to ribisins A and D and corrections to those originally assigned to congeners B and C. Furthermore, prior to the report of the isolation of ribisin G by Dong et al [2] .…”
Section: Introductionmentioning
confidence: 99%